Financial Attitude and Factors Affecting Savings of the Elderly in Phayao Province - Gongkhonkwa, Guntpishcha (NIDA Business Journal, 2022)
An increasing of the aged in the society of Thailand is an important issue which everyone should pay attention to in financial planning for retirement. Many previous studies have found that most elderly people in Thailand are facing financial problems, such as no incomes and no savings; which causes their life after retirement to become more unstable. Therefore, the purposes of the present research are: 1) to measure the level of financial attitude and, 2) to investigate the causal factors influencing savings. The research was conducted using a multi-stage sampling technique on 387 participants, aged over sixty years old and living in Phayao province. The data were collected by questionnaire, including socio-demographics, savings information, and financial attitudes. Structural equation modeling (SEM) was used to represent the relationships of factors which the results found: Incomes attitudes and savings attitudes of the elderly in Phayao province were at the highest level; which is a good sign because both incomes and savings attitudes have a positive relationship on saving. However, expenditures attitudes and debts attitudes were at the moderate level; which is a bad sign because expenditures and debts attitudes have a negative relationship on saving. The causal relationship model found that both socio-demographic and financial attitude affect saving by the elderly in Phayao province. Moreover, there are two factors that have the greatest effect on savings; financial information, and savings attitudes.